ROLE OF ORGANIZATIONAL COMMITMENT AS MEDIATOR FOR SERVANT LEADERSHIP RELATIONSHIP AND COMPENSATION - Rumbita Febriarukmini; Mulyanah Mulyanah; Luciana Indah Permatasari; Muhammad Fachrudin Arrozi Adhikara; CSP Wekadigunawan (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2023)
This research is based on information from the personnel department regarding problems that describe the low organizational citizen behavior (OCB) of nurses in 2021. The purpose of this study was to obtain empirical evidence of the effect of servant leadership and compensation on OCB with organizational commitment as an intervening variable, using a cross sectional study design. The population in this study were 100 nurses, the sampling technique used a saturated sample which made the entire population a sample. The results of the analysis prove that simultaneously and partially servant leadership and compensation have a positive and significant effect on organizational commitment and OCB, and organizational commitment has a direct positive and significant effect on OCB, and organizational commitment provides positive intervention on the relationship of servant leadership and organizational commitment, so that with commitment organization, nurses are able to increase OCB higher through servant leadership and compensation. The importance of work engagement will bring about a situation where career and leadership development will make nurses' organizational commitment higher in supporting the achievement of organizational goals.